Genetic Algorithm-Based Approach for Minimising Losses in Substrate-Integrated Waveguide - Nur Hidayah Mansor; Razi Abdul-Rahman (IAES Indonesian Section, 2020)
The transitions in air-filled substrate-integrated waveguide (SIW) are studied here for millimetre-wave applications. A good design of an air-filled SIW (AFSIW) must allow for minimum losses in its interconnects between the air-filled and dielectric-filled regions of the SIW. This paper assesses the influence of the geometry of transition taper in an AFSIW on the return and insertion losses using full-wave analysis of a complete AFSIW structure. The data from the return and transmission losses provide a basis in the optimisation of the design of the transition tapers. The optimisation approach uses the multi-objective genetic algorithm (GA) with full-wave analysis to find an optimum profile of the transition. Defining the profile of the transition taper with a clamped cubic spline as a phenotype, the developed procedure shows that further losses are possible within the prescribed frequency bands. Furthermore, the length of the transition taper can be significantly reduced while maintaining an optimal quality of signal transmission in the transition. The simulation results show the efficacy of the proposed strategy where the optimal taper geometry is shown to provide a wider band of operating frequencies with lower return loss compared to a more established taper geometry.